Structural Model of Prediction Wisdom based on Successful Intelligence and Psychological Well-Being with the Mediating role of Self-Efficacy - Derakhshan, Maryam; Nasrolahi, Bita; Bagheri, Fariborz (Applied Family Therapy Journal (AFTJ), 2022)
Aim: This research was conducted with the purpose of presenting a structural model for predicting wisdom based on successful intelligence and psychological well-being with the mediating role of students’ self-efficacy. Methods: The cross-sectional research method is correlation type. The statistical population of this research was made up of all female and male students of Azad Universities of Tehran province in 2019-2019, from which 400 people were selected by staged cluster sampling method. In this research, the tools of wisdom (Ardelt, 2003), successful intelligence (Sternberg, 2005), psychological well-being (Reif, 1989) and self-efficacy (Sherer et al., 1982) were used, all of which had acceptable validity and reliability. In order to analyze the data, SPSS-V19 and Amos-V8.8 software were used. Also, in order to respond to the research hypotheses, structural equation modeling was used. The findings of the research showed that the model has a good fit. Results: The results showed that successful intelligence has a direct effect on wisdom, the relationship between successful intelligence and wisdom is directly equal (t = 2.08 and β = 0.25). In connection with the existence of an indirect effect of successful intelligence on the wisdom of students through self-efficacy, it is rejected with 95% confidence. The results showed that psychological well-being had a direct effect on wisdom, the relationship between psychological well-being and wisdom is directly equal (t = 4.91 and β = 0.68). In connection with the existence of an indirect effect of psychological well-being on the wisdom of students through self-efficacy, it is confirmed with 95% certainty. Conclusion: Therefore, paying attention to the mentioned variables helps researchers and therapists in prevention and designing more appropriate treatments.